Effect of Poultry Guard Litter Amendment on Horizontal Transmission of Salmonella enteritidisin Broiler Chicks - Vicente, J.L.; Higgins, S.E.; Hargis, B.M.; Tellez, G. (International Journal of Poultry Science, 2007)
To evaluate the effect of a litter acidifier (PGLA) on Salmonella enteritidis(SE) horizontal transmission, two experiments were conducted with broiler chicks grown on used (Exp. 1) and new (Exp. 2) litter. In each experiment, three hundred day-old broiler chicks from a commercial hatchery were obtained and divided into three litter treatments with four replicate pens each. The treatments were: control (no litter treatment); low dose of PGLA (LD: 815g/2.27m2); and high dose (HD: 1631 g/2.27m2). In Exp. 1, two hundred-forty chicks were placed in floor pens with pine shaving-based litter previously used for at least two prior growouts (20 chicks/pen). Another 60 chicks were challenged with 7.5×103 cfu of SE (seeders), placed in a separate pen with clean new pine shaving-based litter for 24 hours, then 5 seeders (20%) were placed with the contact chicks in each respective treatment pen. Salmonella recovery from cecal tonsils of 10 chicks/ pen were evaluated on days 11 and 21. Application of PGLA at both LD and HD on used litter significantly reduced (p